2022
DOI: 10.1007/s12012-022-09771-5
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 Knockdown Can Improve Myocardial Ischemia/Reperfusion Injury by Inhibiting Autophagy

Abstract: Background and Aim: This study aims to investigate the effect and mechanism of proprotein convertase subtilisin/Kexin type 9 (PCSK9) on myocardial ischemia-reperfusion injury (MIRI) and provide a reference for clinical prevention and treatment of acute myocardial infarction (AMI).METHODS: We established a rat myocardial ischemia/reperfusion (I/R) model and AC16 hypoxia/reoxygenation (H/R) model. A total of 48 adult male Sprague-Dawley rats were randomly assigned to three groups (n=16): control, I/R, and I/R +S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…PCSK9 knockdown in adult rats alleviated myocardial injury induced by occlusion of the left anterior descending (LAD) branch. This protective effect was attributed to the repression of the Bnip3 autophagy pathway and inhibition of the inflammatory response [126].…”
Section: Myocardial Ischemia-reperfusion Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…PCSK9 knockdown in adult rats alleviated myocardial injury induced by occlusion of the left anterior descending (LAD) branch. This protective effect was attributed to the repression of the Bnip3 autophagy pathway and inhibition of the inflammatory response [126].…”
Section: Myocardial Ischemia-reperfusion Injurymentioning
confidence: 99%
“…In an ischemic or hypoxic heart, the expression of many mitochondria-related enzymes and genes is increased, which causes mitochondrial dysfunction in cardiac muscle cells leading to myocardial damage [124][125][126]. In response to ischemic stress, proprotein convertase subtilisin/kexin type 9 (PCSK9) expression is strongly upregulated in the border region of infarcted mouse hearts, and autophagy ensues [124].…”
Section: Myocardial Ischemia-reperfusion Injurymentioning
confidence: 99%
“…It is noteworthy that high expression of PCSK9 after myocardial infarction promotes pro-inflammatory M1 macrophage polarisation associated with poor myocardial repair, whereas PCSK9 deficiency promotes anti-inflammatory M2 macrophage polarisation and better protection against myocardial injury (54). Inhibition of PCSK9 has been shown to ameliorate myocardial injury after ischaemia/reperfusion by inhibiting autophagy and inflammation (55).…”
Section: Pcsk9 and The Heartmentioning
confidence: 99%
“…Autophagy serves a crucial role in maintaining intracellular homeostasis by eliminating harmful cytoplasmic components through autolysosomes . Recent studies have revealed that stem cells, including MSCs, experience cellular senescence at an early stage, a phenomenon closely associated with impaired autophagy function. , MSCs obtained from older donors exhibited compromised autophagy capabilities.…”
Section: Introductionmentioning
confidence: 99%